PS-042c is low-dose combined oral contraceptives use associated to lower bone mineral content variation in adolescents over a one-year period? - Goldberg, Tamara Beres Lederer [UNESP]; Biason, T. [UNESP]; Kurokawa, C. [UNESP]; Moretto, M. [UNESP]; Teixeira, A. [UNESP]; Nunes, H. [UNESP] (BMJ, 2014)
Background Low dose combined oral contraceptives (COC) can interfere in bone mass acquisition during adolescence. To evaluate bone mineral density (BMD) and bone mineral content (BMC) in female adolescents taking a standard low-dose (EE 20 µg/Desogestrel 150 µg) combination oral contraceptive (COC) over a one-year period and compare with healthy adolescents from the same age group not taking COCs.Methods A non-randomised parallel control study with one-year follow-up. Sixty-seven adolescents from 12 to 20 years of age, divided into COC users (n = 41) taking 20 µg EE/150 µg Desogestrel and non-user controls (n = 26), were evaluated through bone densitometry examinations at baseline and 12 months later. Comparisons between groups at study start was done through the Mann-Whitney test with significance level fixed at 5% or corresponding p value; comparisons between groups at study start and 12 months later used variations in median percentages for bone mass variables.Results COC users presented low bone mass acquisition in the lumbar spine and BMD and BMC median variations between baseline and at 12 months of 2.07% and +1.57% respectively whereas the control group presented variations of +12.16% and +16.84% for BMD and BMC, respectively, over the same period. The total body BMD and BMC presented similar evolution during the study in both groups. Statistical significance (pConclusion The use of a low COC dose (EE 20 µg/Desogestrel 150 µg) was associated to lower bone mass acquisition in adolescents during the study period.Trial registration: (Register Number):RBR-5 h9b3c
Keywords: Adolescents; Bone mass; Contraceptive